2021
DOI: 10.1016/j.eats.2020.10.052
|View full text |Cite
|
Sign up to set email alerts
|

All-Inside Anterior Cruciate Ligament Reconstruction With Augmentation Using the Native Anterior Cruciate Ligament Remnant by Suture Approximation

Abstract: Anterior cruciate ligament (ACL) rupture remains a debilitating orthopaedic pathology with a substantial economic and psychological burden on patients, especially athletes. The purpose of ACL reconstruction is to attain maximum joint stability and functionality, allowing patients to resume their previous level of activity. Several graft options and techniques are available for ACL reconstruction. The all-inside remnant-preservation technique is a minimally invasive approach aiming for improved proprioception, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…[3][4][5][6][7] In the previous literature, internal brace augmentation was performed by using FiberTape (Arthrex) to protect the ACL graft and could augment the graft with biologic tissue such as amnion, or bone marrow concentrate. [8][9][10]12,13 However, in a cadaveric study, Lai et al 14 showed that suture augmentation also improved the ultimate load to failure and cyclic displacement in ACL grafts. There was also a surgical technique using multiple suture strands to augment ACL which was reported by Kuptniratsaikul et al 15 The suture acts as a structural tie before fully ligamentization of the ACL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] In the previous literature, internal brace augmentation was performed by using FiberTape (Arthrex) to protect the ACL graft and could augment the graft with biologic tissue such as amnion, or bone marrow concentrate. [8][9][10]12,13 However, in a cadaveric study, Lai et al 14 showed that suture augmentation also improved the ultimate load to failure and cyclic displacement in ACL grafts. There was also a surgical technique using multiple suture strands to augment ACL which was reported by Kuptniratsaikul et al 15 The suture acts as a structural tie before fully ligamentization of the ACL.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous literature, internal brace augmentation was performed by using FiberTape (Arthrex) to protect the ACL graft and could augment the graft with biologic tissue such as amnion, or bone marrow concentrate. 8 , 9 , 10 , 12 , 13 However, in a cadaveric study, Lai et al. 14 showed that suture augmentation also improved the ultimate load to failure and cyclic displacement in ACL grafts.…”
Section: Discussionmentioning
confidence: 99%
“…This concept has led to increased interest in studies of remnant preservation, proven by the recent surge in publications in the field of repair and remnant preservation. 2 , 3 , 6 , 7 , 8 , 12 Because of newer information about the remnant, ACL is now considered as an organ with neural and vascular tissues and not merely a stabilizing structure. 11 Many histologic studies have confirmed that remnants of torn ACL retain vascularized synovial sheets, numerous fibroblasts and myofibroblasts, and various mechanoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these techniques vary in femoral fixation methods. 7 Aperture fixation with interference screw on femoral side is a straightforward technique and found to have similar clinical or radiographic outcome compared with cortical suspensory button fixation. 9 In our technique, we pulled the sutures holding the remnant through the femoral tunnel along with the hamstring graft and fixed it with an interference screw.…”
mentioning
confidence: 98%
See 1 more Smart Citation